Wealth, health, and inequality: a study of hyperinflation and households in Zimbabwe - Kurasha, Flora Marvellous Nyasha (School of Economics, 2021)
This study focuses on Zimbabwe's first hyperinflation which began in March 2007 and peaked at 231 million percent in July 2008. Through a comparative pre-post analysis, the study investigates hyperinflation's effects on the well-being of households, its empirical chapters assessing changes in asset poverty, asset inequality and child malnutrition before and after the hyperinflation. The first empirical chapter assesses the shifts in asset poverty. Household holdings of physical assets and recorded access to public utilities are drawn from the 1994, 1999, 2005 (prehyperinflation) and the 2010 and 2015 (post-hyperinflation) Zimbabwe Demographic and Health Survey datasets. These are used to construct an asset index, with the 20th and 40th percentiles as relative poverty lines. Asset-derived poverty headcount and poverty gaps are measured and compared across the two periods. The national asset poverty headcount ratio decreased by 27 percent largely driven by of the experience of rural households whose asset poverty headcount fell by 31 percent. In contrast urban households experienced a 51 percent increase in asset poverty in this period. The second empirical chapter assesses the shifts in asset inequality during the hyperinflation. Rather than focus on income inequality, it continues using asset holdings and constructs pre- and post-hyperinflation asset Gini coefficients for urban and rural households. These show decreased asset inequality during the hyperinflationary period. At a national level, inequality decreased by 7 percent and in rural areas by 2 percent. The decrease in inequality on a national level was mainly attributable to the increase in private assets among rural households. However, there was a 2 percent increase in inequality among urban households, largely attributable to ownership of private assets. Land and livestock were the main drivers of inequality. The final empirical chapter focuses on the changes in child nutrition during the hyperinflation, and the factors contributing to these changes amongst children under the age of 5. Using Mosley and Chen's (1984) proximate determinants analytic framework, multivariate Logistic regression analyses revealed that wasting and stunting increased with inflation. Other related factors were poor access to electricity, safe drinking water, improved toilets and healthcare, as well as low levels of mother's education and asset wealth.